An offensive realism analysis of the Kashmir conflict: Power politics and regional hegemony in South Asia - Jaafar, Faridah; Radzi, Shamsul Azri Mohd (Masyarakat, Kebudayaan dan Politik, 2025)
The Kashmir dispute is one of the longest standing territorial disputes in the modern international system, and an interesting case study to test the explanatory value of the offensive realism theory. This article examines the Kashmir dispute using the theoretical framework of John J. Mearsheimer to look at the ways in which the power maximization strategies and hegemonic ambitions have influenced the relationship between India and Pakistan since 1947. The research utilizes a qualitative research design which is grounded in secondary data analysis and thematic analyses of archival documents and literature. The results show that offensive realism is a superior explanation for the continuity of the conflict by illustrating the nature of structural imperatives of the anarchic international system that perpetuate the aggressive behaviors of India and Pakistan for achieving regional hegemony. The existence of the security dilemma in their relations has established a vicious cycle of distrust and competition, while nuclear arms have paradoxically limited and deepened their rivalry. By showing how realist structural theories are still pertinent for the analysis of contemporary conflicts in the region, this analysis contributes to international relations scholarship and provides policy implications for the management of longstanding rivalries in anarchical systems.